COMPARATIVE PRODUCTION PERFORMANCE OF FOUR DIFFERENT NAKED NECK CHICKEN PHENOTYPES IN PAKISTAN - M. Shafiq; A. Mahmud; J. Hussain; A. Basheer; S. Mehmood; M. T. Khan; S. Ahmad; M. Asif (Journal of Animal and Plant Sciences, 2018)
A study was conducted to evaluate the production performance in four different phenotypes of naked neck chicken. In total, 300 females (20 weeks old) from four different phenotypes (black, white black, light brown and dark brown), 75 from each, were randomly assigned to four experimental groups arranged in a Completely Randomized Design (CRD). Each treatment was replicated 5 times with 15 birds in each. Feed intake, body weight, egg production, egg weight, egg mass, FCR/dozen eggs, FCR/kg egg mass and livability were evaluated. The data were analyzed using ANOVA technique. The result indicated significantly (P≤0.05) higher feed intake in white black phenotype, heavier body weight in light brown and dark brown phenotypes whereas, egg production, egg mass, FCR/dozen eggs and FCR/kg egg mass were found to be better in light brown phenotype. Egg weight remained higher in black, light brown and dark brown phenotypes. In conclusion, light brown phenotype demonstrated overall better production performance as compared to others.
Keywords: Production performance; Naked-neck; Phenotype; Livability